Kriteria Kesahihan Hadis Menurut Nashiruddin Albani dan Ahmad Al-Ghumari - Mia Syahrina Hanifa; Ali Masrur; Badri Khaeruman (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study is to find out the criteria for the validity of hadith according to Nashiruddin Albani and Al-Ghumari and to find out the differences and similarities of the criteria for the validity of hadith according to Nashruddin Albani and Al-Ghumari. The research method used is comparative study. The results of this study showed that technically, the two hadith scholars have their own characteristics in researching the validity of a hadith. The criteria of shahih hadith according to the two hadith scholars do have similarities and differences with some other hadith scholars so as to cause some controversy.